Association Between Spousal Loss and Depression Among Older Adults: A Cross-Sectional Study in Geulanggang Teungoh Village, Aceh, Indonesia - Muakhir Syah Putra; Adelia Silfana Nasution; Maisura Maisura; Mahadzir ZA (STIKep PPNI Jawa Barat, 2026)
Background: The growing elderly population has increased the number of older adults experiencing spousal loss, a major life event that may adversely affect psychological well-being and increase the risk of depression. Evidence from rural communities with strong cultural and family support systems, such as those in Aceh, Indonesia, remains limited. Objective: This study aimed to examine the association between spousal loss and depression among older adults in a rural Acehnese community. Methods: A quantitative analytical study with a cross-sectional design was conducted among 48 older adults who had experienced spousal loss, selected through total sampling. Data were collected using structured interviews, a respondent characteristics questionnaire, a researcher-developed spousal loss questionnaire, and the Geriatric Depression Scale (GDS-15). Descriptive statistics summarized participant characteristics, while the association between spousal loss and depression was analyzed using the Lambda contingency coefficient with a significance level of 0.05. Results: Most participants were women (87.5%), aged 60–74 years (56.2%), and had experienced spousal loss for more than two years (70.8%). Mild depression was the most common condition (47.9%), followed by moderate depression (37.5%), whereas most participants had normal cognitive function (79.2%). A statistically significant association was found between spousal loss and depression (p = 0.026). Conclusion: Spousal loss was significantly associated with depression among older adults in this rural community. Although the cross-sectional design precludes causal inference, the findings highlight the need for early depression screening, family-centered support, psychosocial interventions, and community-based gerontological nursing programs to promote the psychological well-being of bereaved older adults